STABILISASI TANAH DENGAN FLY ASH DAN SEMEN UNTUK BADAN JALAN PLTU ASAM-ASAM - Huri, Andreas Dharmawan; Yulianto, Kristian; Retno Wardani, Sri Prabandiyani; Hardiyati, Siti (Jurnal Karya Teknik Sipil, 2013)
The huge amount of coal waste (fly ash) produced by Acid plant could be use the main material for soil stabilizing at thr road ro plant acids Because it has the CBR value ≤ 6% is 3.52% roomates minimum limits allowed by SNI 03-1744-1989 and also to solve enviromental pollution problems, but certainly how much fly ash is used in order not to polute the environment Necessary to conduct futher research.In this research, the chemical stabilization method used to repaired the base soil condition is by the base soil mix with a combine of protland cement and fly ash as stabilizing agent in various ratios; 4% PC + 5% FA, 4% PC + 8 % FA, 4% PC + 10% FA, 2% PC + 7% FA, and 4.5% PC + 8% FA by weight of dry soil. The result of original soil tests indicate the clasification is clay with high plasticity (CH) According to the Unified System and grade A-7-6 According to AASHTO. The result of CBR test with various mixed ratio in soaked condition by 0, 4, and 7 days show the CBR value is increasing. The maximum increase of is%, happened in various optimum mix ratio of 4% PC + 8% FA for 4 days of soaked time. The conclusion is that the optimum use of fly ash at 8% could be used to solve environmental pollution problems and also used as stabilizing agent at the road to the power plant Acid.